Kaposi`s varicelliform eruption in a case of pustular psoriasis - Rao, Naveen Netaji; Toor, Sharanjit Singh (International Journal of Research in Dermatology, 2022)
Kaposi`s varicelliform eruption (KVE) is a disseminated cutaneous infection with herpesvirus type 1 or 2, vaccinia virus, or coxsackievirus A16 in a patient with another underlying dermatosis. When herpesvirus type 1 or 2 is the pathogenic virus, the term ‘‘eczema herpeticum’’ (EH) is used, independent of the underlying dermatologic diagnosis that preceded the eruption. Presenting a case of generalised pustular psoriasis who while on immunosuppressant therapy cyclosporine developed KVE on the 3rd week of therapy. Based on the nature of cutaneous eruption and the bed side Tzanck smear test he was diagnosed as Psoriasis herpeticum. He was treated with oral acyclovir for 15 days with complete resolution of the lesions. KVE rarely occurs in psoriasis. It is more often in those patients who are on immunosuppressant therapy like oral methotrexate, cyclosporine etc. A high index of suspicion is needed while managing skin eruptions in a known case of psoriasis.